Studi Kasus Pelaksanaan Evaluasi Pembelajaran Pendidikan Agama Islam (PAI) di SD N 22 V Koto Kampung Dalam - Arbi Salam Ahmad; Remiswal; Khadijah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study is motivated by the importance of conducting comprehensive and systematic evaluations in Islamic Religious Education (PAI) instruction, encompassing the cognitive, affective, and psychomotor domains. The study aims to describe the implementation of PAI learning evaluations at SD N 22 V Koto Kampung Dalam. A descriptive qualitative method with a case study approach was employed. The research subject was a single PAI teacher selected through purposive sampling. Data were collected via observation, in-depth interviews, and documentation, then analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which involves data condensation, data display, and conclusion drawing and verification. The results indicated that the learning evaluation is carried out in three stages: planning, implementation, and follow-up. Planning involves the preparation of evaluation tools; implementation entails assessing the cognitive, affective, and psychomotor domains; and follow-up is realized through remedial programs, enrichment activities, and instructional improvements. The study concludes that, while PAI evaluations at the school generally cover all three learning domains, there remains a need to develop assessment instruments, enhance consistency in affective and psychomotor assessments, and provide adequate learning facilities specifically, a prayer room (mushala) within the school premises